The Promising Effect of Nerve Decompression in Trigeminal Autonomic Cephalalgias: Report of Case Series - Togha, Mansoureh; Totonchi, Ali; Molaei, Hojjat; Ansari, Hossein (Frontiers in Neurology, 2021)
Trigeminal Autonomic Cephalalgias (TAC) are excruciating headaches with limited treatment options. The chronic forms of TACs, including chronic cluster, chronic paroxysmal hemicrania, and hemicrania continua, are disabling conditions. In addition to drug therapy, there are some studies regarding nerve blocking and nerve stimulation with acceptable results. Here we report four cases of decompression nerve surgery with promising results on pain control in these difficult to treat headaches.